Constitutional Analysis of the Indonesian Ulema Council Role in Political Mass Gatherings Minangkabau Region - Ainul Mardhiah; Ahmad Suryadi (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
The controversy surrounding the refusal of the Majelis Ulama Indonesia (MUI) of Payakumbuh City to issue a recommendation for a *tabligh akbar* led by Ustadz Abdul Somad (UAS) during the local election period highlights a persistent tension between the protection of constitutional rights and efforts to maintain the political neutrality of places of worship. MUI Payakumbuh asserted that the decision did not target religious preaching per se, but rather aimed to prevent indications of covert political campaigning conducted under the guise of religious gatherings in mosques. This study examines the legal basis and constitutional legitimacy of MUI’s action, maps the local political dynamics of Minangkabau society that shape the controversy, and assesses its implications for freedom of religion, expression, and the regulation of religious spaces in electoral contexts. The study employs a qualitative normative-empirical approach. Primary data were collected through in-depth interviews with MUI officials and mosque administrators in Payakumbuh, while secondary data consist of MUI fatwas and recommendations, electoral regulations (Law No. 7 of 2017, KPU and Bawaslu regulations), and national and local media reports. Data were analysed using statutory analysis, case study methods, and critical discourse analysis. The findings indicate that the prohibition of political campaigning in places of worship has a strong normative foundation in electoral law. However, from a constitutional perspective, MUI’s intervention risks regulatory overreach when the notion of practical politics is applied without clear, objective criteria and accountable procedures.